"This won't hurt a bit". (December 2013) - Brakoulias, Vlasios
Background: In our quest to improve the lives of our patients, we can often be swept up by the euphoria associated with new treatments. At times, our enthusiasm for new treatments can lead us to forget the fundamental principles of patient care and lose focus of an individual's suffering and personal journey. Objective: To illustrate the importance of understanding a patient's predicament in the context of our own need to cure. Methods: Oil on canvas (92 × 122cm). Results: By focusing on a centrally positioned patient who has hypothetically just had new electronic devices installed into her scalp and chest wall, I was able to see a weakened lady with a turbulent past attempting to protect herself with her jet black hair. Many around her remain oblivious to the storm. An observant medical student glances away from his textbook to see that all is not well outside the hospital walls. Conclusions: Several perspectives are required to adequately assess the way that we treat patients. Contrary to our expectations, our treatments might hurt a bit.